Assessment of Fufu Production Technologies in Ogun State, Nigeria - Owolarafe, O. K.; Adetifa, B. O.; Oyekanmi, A. C.; Lemikan, T. G.; Samuel, T. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
The quality of fufu has been known to vary from one location to another. The processing technique may be responsible for this variation in quality. A study was carried out to investigate the different processing technologies adopted for production of fufu from cassava at different processing centres in Abeokuta and Ilaro, Ogun State. Hundred fufu processing centres were randomly selected, while data was collected using structured questionnaire, sensory analysis and physical observation. Information about the ownership, operator, enterprise, source of water supply, unit operations alongside their equipment and the waste disposal methods were gathered. Results showed that most fufu processing centres were owned by individuals. Most of the unit operations were carried out manually usually by women with low education level. Plastic drums and concrete pots were commonly used for soaking cassava for 3-5 days. Cassava mash is sun-dried for an average of 2.79±1.1 days and packaged into nylon or jute bags. Cassava peel and chaff are often reused while the wastewater is either drained into pits or left unattended to. Delay in processing cassava tubers, increase in the length of soaking, ineffective dewatering method, unhygienic source of water for fufu processing, etc. were some of the factors observed to affect the physical quality of fufu. Statistical analysis shows that the categories in most of those unit operations do not have equal probabilities of occurrence in the population. It is therefore imperative to develop appropriate technologies affordable by the small scale processors for the people in the area.